섬쑥부쟁이 주정추출물과 비타민 B 복합물 병용에 의한 인지개선 상승효과 - 정정호(Jeongho Jeong); 임미경(Mi Kyung Lim); 이소연(Soyeon Lee) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2022)
본 연구에서는 섬쑥부쟁이 70% 주정추출물 및 비타민 B 복합물 투여에 의한 인지기능 개선 효능을 확인하고자 하였다. 먼저 Morris water maze test를 통해 기억손상 마우스 모델에서 섬쑥부쟁이 70% 주정추출물 투여에 의해 장기 기억력 및 공간 기억력이 향상됨으로써 인지기능 개선 기능성 소재에 대한 가능성을 확인하였다. 이에 추가로 in vitro 모델에서 섬쑥부쟁이 70% 주정추출물의 신경세포사멸 억제 효과를 확인하였으며, 더불어 비타민 B 복합물과의 병용 처리를 통해 상승효과가 발생하는 것을 확인하였다. 이러한 실험 결과를 바탕으로 기억손상 마우스 모델에서 섬쑥부쟁이 70% 주정추출물 및 비타민 B 복합물 투여에 의한 인지개선 효능을 평가한 결과, 섬쑥부쟁이 70% 주정추출물 및 비타민 B 복합물 단독 투여에 의해 scopolamine 유도군 대비 AChE 활성이 저하되고 ACh 함량이 증가하였으며, 두 시료를 병용하여 투여하였을 때 상승효과가 발생하는 것을 확인하였다. 본 연구 결과는 in vitro 및 in vivo 실험에서 장기 기억력 및 공간 기억력 개선, 신경세포사멸 억제, AChE 활성 억제 및 ACh 함량 증가를 통해 인지기능 개선에 도움을 주는 기능성 소재로서 섬쑥부쟁이 70% 주정추출물의 개발 가능성을 보여주었다. 또한 섬쑥부쟁이 70% 주정추출물과 비타민 B 복합물의 병용 시 이러한 기능성이 더욱 상승하는 것을 확인하였으므로 이를 인지개선에 효과적인 기능성 제품 및 여러 가공품 개발에 적극 활용할 수 있을 것으로 기대된다. Aster glehni Franchet et Sckmidt is mainly grown in Ulleungdo Island, Republic of Korea. It has been known as a medicinal herb that relieves frequent coughing, high fever, and severe pain. Although several recent studies have reported that Aster glehni might have neuroprotective and memory-enhancing effects, research on the effects of improving cognitive function is insufficient. This study was therefore undertaken to investigate whether ethanolic extracts from leaves and stems of Aster glehni (EAG) have an effect on improving cognitive functions, through in vitro and in vivo assays. In addition, synergistic effects on cognitive improvement were evaluated by applying a combination of EAG with the vitamin B complex (VBC). The in vivo studies determined that EAG exerts cognitive improvement effects by reducing escape latency and increasing the time spent in the platform quadrant in the Morris water maze test. EAG treatment also inhibited acetylcholinesterase activity and increased the level of acetylcholine in mouse brain tissues. Moreover, we observed a protective effect against β-amyloid-induced neurotoxicity in human neuroblastoma cells. These effects were further enhanced when combined with VBC. Therefore, these findings indicate that EAG treatment in combination with VBC has the potential to improve cognitive function more effectively than a single treatment. KCI Citation Count: 3